Guignon C. Authenticity / trans. from Engl. R. L. Kochnev - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
This article discusses the ordinary, the existentialist, and the virtue-ethics senses of the word ‘authenticity’. The term ‘authentic’ in ordinary usage suggests the idea of being ‘original’ or ‘faithful to an original’, and its application implies being true to what someone (or something) truly is. It is important to see, however, that the philosopher who put this technical term on the map in existentialism, Martin Heidegger, used the word to refer to the human capacity to be fully human, not to being true to one’s unique inner nature. Authenticity might also be thought of as a virtue, and interesting questions arise whether such a virtue should be regarded primarily as a personal or as a social virtue